2018
DOI: 10.1007/s11523-018-0561-6
|View full text |Cite
|
Sign up to set email alerts
|

Atezolizumab in Metastatic Urothelial Carcinoma Outside Clinical Trials: Focus on Efficacy, Safety, and Response to Subsequent Therapies

Abstract: Patients with mUC who progressed on atezolizumab were unlikely to receive subsequent systemic treatments and the benefit of those treatments appeared limited in our cohort. The findings may impact timing and designs of clinical trials in mUC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Thus, patients with PS 2 in the KEYNOTE‐045 trial differ significantly from the actual population of patients with UC and PS 2. Four retrospective studies have assessed efficacy of ICIs in patients with UC and PS ≥2, including any ICI 8 in one study and atezolizumab in three studies 9‐11 . Khaki et al reported a median OS of 8.2 months and ORR of 23% among patients with PS ≥2 and who received an ICI in the second‐line setting or later, which were comparable to the outcomes for patients with PS ≤1 8 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, patients with PS 2 in the KEYNOTE‐045 trial differ significantly from the actual population of patients with UC and PS 2. Four retrospective studies have assessed efficacy of ICIs in patients with UC and PS ≥2, including any ICI 8 in one study and atezolizumab in three studies 9‐11 . Khaki et al reported a median OS of 8.2 months and ORR of 23% among patients with PS ≥2 and who received an ICI in the second‐line setting or later, which were comparable to the outcomes for patients with PS ≤1 8 .…”
Section: Discussionmentioning
confidence: 95%
“…Conversely, a study of atezolizumab therapy in patients with advanced UC or non‐UC (SAUL study) reported a median OS of 2.3 months and ORR of 5% in patients with PS 2 9 . The other two studies did not focus on patients with PS ≥2, and the reported ORR for the entire cohorts ranged from 17 to 21% 10,11 . These widely divergent outcomes might be attributable to differences in patients’ backgrounds such as the number of risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Similar multicenter experiences previously reported in the literature suggested that patients progressing to frontline ICI are not likely to receive or benefit from subsequent chemotherapy. 14,18 With the MeeT-URO 1 population, we obtained different results, showing a quite favorable outcome of patients treated with chemotherapy after progressing to ICI. Indeed, the outcome in terms of median PFS (3.5 months) and median OS (9 months) in the overall population was not inferior to that expected from salvage chemotherapy after the first-line polychemotherapy Abbreviations: N, total number of patients; NE, not evaluable; PD, progression of disease; PR, partial response; SD, stable disease.…”
Section: Discussionmentioning
confidence: 97%
“…The study of atezolizumab in locally advanced or metastatic urothelial or non‐urothelial carcinoma of the urinary tract (SAUL study), investigated worldwide safety and efficacy of atezolizumab, enrolled 101 patients with an ECOG PS of 2 and noted an ORR of 5% and median OS of 2.3 months. Barata et al reported a single‐institution series of 79 patients with aUC treated with atezolizumab, including 24% with an ECOG PS ≥ 2, and they reported an ORR for the entire cohort (including an ECOG PS of 0‐1) of 18%. Pal et al reported outcomes from an expanded‐access program with atezolizumab, which included 20 patients with an ECOG PS ≥ 2, and they noted an ORR of 17% among all patients with evaluable disease (including an ECOG PS of 0‐1).…”
Section: Discussionmentioning
confidence: 99%